Biological monitoring as a valid tool to assess occupational exposure to mixtures of 2,4-:2,6-toluene diisocyanate / Validità del monitoraggio biologico per la valutazione dell’esposizione professionale a miscele di 2,4-:2,6-toluendiisocianato - De Palma, Giuseppe; Cortesi, Ilenia; Ghitti, Roberta; Festa, Denise; Bergonzi, Roberto; Apostoli, Pietro (La Medicina del Lavoro, 2012)
Summary Background and Objectives: Despite its advantages over environmental monitoring, biological monitoring of exposure to 2,4-:2,6-toluene diisocyanate (TDI) mixtures is still underused. The present study was designed in order to evaluate the feasibility and reliability of biological monitoring in a factory producing polyurethane foam blocks. Methods: Airborne TDI isomers were sampled by both static and personal pumps and determined by HPLC with fluorimetric detection. Specific metabolites 2,4- and 2,6-toluenediamine (TDA) were determined by gas chromatography-mass spectrometry on hydrolysed urine samples collected from 16 workers at the beginning of the workweek and both before (BS) and at the end (ES) of the 4th workday. Additional samples were collected at the end of the 1st half-shift and at the beginning of the 2nd half-shift in 5 workers. Results: In the foam production shop, TDI values were on average about 20 mg/m3, with higher levels in the 2nd half-shift and peak levels in workers operating along the polymerization tunnel. Average TDI levels were significantly correlated with ES TDA concentrations (p<0.0001). TDA showed a fast urinary elimination phase leading to progressively higher TDA levels either during the shift (5 workers) and at the end-of-shift. A slower elimination phase with a weekly accumulation was demonstrated by values at the beginning of the workweek (higher than in unexposed subjects) and by their elevation in subsequent BS samples. Conclusions: The study demonstrates the feasibility and reliability of biological monitoring in workers exposed to 2,4-:2,6-TDI mixtures. This approach can provide information about both the daily and weekly exposure levels. Riassunto «Validità del monitoraggio biologico per la valutazione dell’esposizione professionale a miscele di 2,4-:2,6-toluendiisocianato». Introduzione e Obiettivi: Rispetto al monitoraggio ambientale, il monitoraggio biologico dell’esposizione professionale a miscele di 2,4-:2,6- toluendiisocianato (TDI) è ancora scarsamente utilizzato. Il presente studio è stato condotto in una fabbrica di poliuretano espanso, con lo scopo di verificarne fattibilità e validità. Metodi: I livelli aerodispersi di TDI campionati con postazioni fisse e con campionatori personali sono stati determinati in HPLC con rivelazione fluorimetrica. I metaboliti specifici 2,4- e 2,6-toluendiamina (TDA) sono stati determinati in gas-cromatografia accoppiata alla spettrometria di massa, dopo idrolisi dei campioni urinari raccolti da 16 lavoratori a inizio turno (IT) inizio settimana lavorativa e ad IT e fine turno (FT) del 4o giorno lavorativo. Su cinque lavoratori, le urine sono state raccolte anche alla fine del 1o emiturno ed all’inizio del 2o. Risultati: In produzione, i livelli di TDI erano mediamente pari a circa 20 mg/m3, con valori maggiori nel 2o emiturno, rispetto al 1o e picchi di esposizione negli addetti al tunnel di polimerizzazione. I livelli di TDI erano significativamente correlati con le concentrazioni urinarie di TDA FT (p<0.0001). L’eliminazione urinaria della TDA era difasica, con una fase rapida dimostrata dai livelli progressivamente crescenti durante il turno e a FT, rispetto ai valori IT. La fase di eliminazione più lenta era dimostrata dai valori di inizio settimana lavorativa, superiori a quelli riscontrati in soggetti non esposti e dall’aumento significativo dei livelli di IT durante la settimana. Conclusioni: I risultati confermano la validità del monitoraggio biologico dell’esposizione professionale a miscele 2,4-:2,6-TDI, i cui risultati possono fornire informazioni sui livelli di esposizione giornalieri e settimanali.